Do rope and washer pumps provide safe water and satisfied users? A case study piloting new rural water supply technology in Rumphi District, Malawi - Mkandawire, Jacob C; Tembo, Mavuto; Nhlema, Muthi; Luhanga, Joel; Holm, Rochelle H (Water SA, 2019)
Innovation is needed to develop rural water supply to support sub-Saharan Africa communities that are hard to reach. The purpose of this study was to critically review rope and washer pumps that have been installed on manually drilled boreholes in 48 communities as part of a pilot project in Rumphi District, Malawi, and which serve as a sustainable source of drinking water from both technical (water quality and functionality) and social (user satisfaction) perspectives. At each water source, an infrastructure checklist was used (n = 48); 10 users were interviewed (n = 472); and, if the pump had water, water quality samples were collected (n = 24). The results show that use of a professional driller does not guarantee a functioning rope and washer pump that produces safe water. Where the pumps were functional, most provided safe drinking water. However, only 8% (4/48) of pumps had good water quality, a flow rate of >20 L/min and a full consensus of positive satisfaction among users. Pumps are not necessarily working better or worse in more remote areas. A process of introducing and creating evaluative guidelines for new (approved) technologies for rural water supply has not been established in Malawi. Sub-Saharan African governments need to be open to innovative solutions while making sure that standards, including those for functionality, water quality, user satisfaction, private operators, and human capacity for local government regulators, are being followed to ensure safe water for rural communities.